Systematic determination of the optimized Zr content of Ba(ZrxTi1-x)O3 with high dielectric constant at room temperature for high-voltage system application - Kim, Jandi; Seo, Ji Hye; Lee, Sang Heun; Cho, Myunghee; Kwak, Hun; Cheon, Ran Sae; Cho, Seungchan; Cho, Sung Beom; Kim, Minkee; Lee, Yoon Seok; Kim, Yangdo; Choi, Moonhee (Journal of the Korean Ceramic Society, 2024)
In this study, by replacing the B-site element in BaTiO3, a ferroelectric material, with an element with a larger ionic radius, a ferroelectric material with high permittivity at room temperature was synthesized. The powders were prepared by solid-state reaction to perform lattice substitution with Zr4+ (0.72 Å), which has a larger ionic radius than Ti4+ (0.605 Å). To perform effective solid-state reaction and better understand the correlation between variables, this study introduced a design of experiment (DOE) based on the orthogonal array (OA) method included in the PIAno software. By substituting 0.222 mol of Zr, which has a large ionic radius, the crystal structure was deformed through an effective diffuse phase transition (DPT), and this resulted in the largest improvement in permittivity at room temperature. In addition, the powder, which underwent solid-state reaction at 1300 °C, formed the densest structure during sintering, which established the conditions for realizing the best dielectric properties. These results can be utilized as a key material for improving the properties of passive devices used in high-voltage industrial systems in societies undergoing the fourth industrial revolution.
Keywords: Barium zirconate titanates; Ferroelectrics materials; High dielectric constants; High permittivity; High voltage systems; Ionic radius; MLCC; Solid-state reactions; Synthesised; System applications; Barium zirconate titanate; Dielectric; MLCC; Solid-state reaction